A Rare Case of Prolonged Ictal Aphasia. (3rd April 2019) - Katyal, Roohi; De Sousa, Eduardo; Sultan, Fahd
ABSTRACT: Aphasia is commonly seen in focal brain lesions. Prolonged aphasia from an ictal state is rarely reported. We report the case of a 62-year-old man with focal motor status epilepticus manifested initially as episodic right cheiro-oral clonic movements with preserved awareness and expressive aphasia for 48 hours. EEG showed left frontal and central lateralized periodic discharges (LPDs) without plus features (rhythmicity, overlying fast) and electrographic seizures that correlated with right clonic movements. Treatment with two seizure medications (levetiracetam and lacosamide) resulted in complete electrographic and clinical resolution of his symptoms, including aphasia. In this case, aphasia was determined to be an ictal semiology, as patient had complete resolution of his symptoms supported by a normal EEG after receiving seizure medications. We suggest keeping high suspicion for an ictal process in patients with sudden-onset aphasia supported by EEG findings of LPDs.